Dissemination of Influenza A/H5N1 Virus after Intranasal Inoculation of Chickens - O. K. Demina; Ar. A. Sergeev; O. V. P'yankov; A. N. Shikov; Al. A. Sergeev; S. A. Berillo; E. I. Sergeeva; A. P. Agafonov; A. N. Sergeev (Проблемы особо опасных инфекций, 2012)
Studied was dissemination of avian influenza virus (AIV) in the organism of chickens after intranasal challenge with 10-100 LD50. The primary organ of accumulation of AIV A/H5N1 (A/Chicken/Kurgan/05/2005strain) is the respiratory tract (nasal mucosa), where the virus is registered in 18 hours after challenge. The accumulation of pathogen is observed in many organs and serum of chicken in 30-32 hours after challenge. The animals die in 54 hours, the concentration of virus reaches critical value in all studied samples. The highest AIV loads (7 lg of chicken embryo infective dose - EID50/g or ml) are registered in lungs, blood serum and kidneys of chicken. The results of AIV loads measuring using titration and real time RT-PCR show high degree of correlation (r=0.89).